Financial Accountability Grounded in Sharia Values: An Integrative Accounting and English Literacy Perspective within Islamic Economics - Zalikha; Fajrinur; Farhan Zikry (Journal Informatic, Education and Management (JIEM), 2026)
This study examines financial accountability grounded in sharia values from an integrative perspective of accounting and English literacy within the framework of Islamic economics. Financial accountability in Islamic institutions is not merely a technical and administrative obligation, but also a moral and spiritual responsibility rooted in sharia principles such as amanah (trust), ‘adl (justice), and maslahah (public interest). This research employs a qualitative normative approach through library research, analyzing classical and contemporary Islamic economic law sources, accounting literature, and studies on financial literacy and English language use in economic and accounting contexts. The analysis focuses on conceptual foundations, accountability mechanisms, and the role of English literacy in supporting transparent and globally oriented financial communication in Islamic economic practices. The findings indicate that sharia-based financial accountability is constructed through the integration of three interrelated dimensions: accounting accountability, legal–ethical accountability, and communicative accountability supported by English literacy. English literacy plays a strategic role in enhancing transparency, accuracy, and international accessibility of financial reporting in Islamic institutions. This study contributes theoretically by offering an integrative conceptual framework for financial accountability in Islamic economics and practically by providing insights for strengthening governance, transparency, and global engagement of sharia-based organizations.